The relevance of the organisational and geographical dimensions in business networks. (1st January 2011) - Ciabuschi, Francesco
This is a conceptual effort to develop the network perspective in use within the industrial marketing and purchasing (IMP) research tradition by integrating findings from international business (IB) research. An analytical framework to study business network in an international context is developed by considering the implications of the organisational and geographical dimensions of networks. This framework and analytical approach offer broader means of analysis and it also helps tackling network effects and dynamics related to cross-country activities of multinational firms. In relation to the framework a series of propositions and issues for future research are also presented.